Antibacterial Activity of Leaf and Twig Extracts of Castanopsis argentea (Blume) A.DC. Against Escherichia coli and Staphylococcus aureus - Amalia, Alifa; Lailaty, Intani Quarta; Surya, Muhammad Imam; Nuringtyas, Tri Rini; Damayanti, Frisca (Fakultas Biologi Universitas Gadjah Mada, 2025)
Castanopsis argentea is a potential souce of natural antibiotics that has not been studied much. The purpose of this study was to analyze the antibacterial activity and study the content of secondary metabolites from leaves and twigs extract of Castanopsis argentea against Escherichia coli and Staphylococcus aureus bacteria. This study used the paper disk method to see antibacterial activity. Antibacterial activiy was indicated by the formation of a clear zone around the dic paper. Samples were made into three treatments, namely the concentration of 20 mg/ml; 40 mg/ml; and 80 mg/ml. the solvent used was selected based on the level of polarity namely ethyl acetate, 70% ethanol, and aquades. The results of the antibacterial activity test showed that the extract with the most potential to inhibit bacterial growth was ethyl acetate twig extract at a concentration of 80 mg/ml with an average diameter of 6mm for Escherichia coli bacteria and 8.67 mm for Staphylococcus aureus bacteria. The compounds identified in the ethyl acetate twig extract are terpenoids, phenolics, and flavonoids. The results of profiling using UV-Vis spectrophotometry showed that the maximum absorption of terpenoids, flavonoids, and phenolics compounds was found in the wavelength range of 300-600 nm. The secondary metabolite compounds contained in the leaf and twig extracts of Castanopsi argentea make this species a potential natural antibacterial.